The report from ASFA COVID‐19 taskforce: Considerations and prioritization on apheresis procedures during the SARS‐CoV‐2 coronavirus disease (COVID‐19) pandemic. Issue 6 (12th September 2021) - Yamada, Chisa; Hofmann, Jan C.; Witt, Volker; Gupta, Gaurav K.; Winters, Jeffrey L.; ,
Abstract: Since vaccination for SARS‐CoV‐2 coronavirus started, the trajectory of patient numbers infected with the virus has improved once; however, variants of SARS‐CoV‐2 have emerged and more people have been infected; therefore, pandemic status is still far from resolution. Government and social efforts to prevent coronavirus infection continue in most states in the US and globally even after the Centers for Disease Control and Prevention declared some restriction relief for fully vaccinated people in March 2021. Healthcare institutions and various professional organizations have developed guidelines or policies to prevent the spread of these coronaviruses in the setting of apheresis. In this report, the issues that apheresis services may encounter under the current COVID‐19 (SARS‐CoV‐2 coronavirus disease) pandemic will be discussed with potential strategies that can be adapted for efficient and optimum use of apheresis resources.